The Effect of Work Environment and Workload on Employee Performance at KSU Islah Citra Mandiri Ampel Boyolali - Richard William Kaope; Ocky Sundari (Jurnal REKOMEN (Riset Ekonomi Manajemen), 2021)
This research aims to analyze the impact of work environment and workload on employees' work performance. The research object is KSU Islah Citra Mandiri employee in Boyolali. The population was KSU Islah Citra Mandiri Boyolali employees with a total number of 32 people, the samples of which were taken by use of saturated sampling technique. Primary data were collected using questionnaire and analyzed by multiple linear regression to examine the impact of work environment and workload to employees' work performance. The research results indicated that the work environment and workload influence employees 'performance both partially and simultaneously: the work environment has positive impact, while workload has negative impact on employees' performance.